Lead- and copper-complexing extracellular ligands released by Kirchneriella aperta (Chloroccocales, Chlorophyta) - Lombardi, A. T.; Vieira, A. A. H. (Taylor & Francis, 1999)
The freshwater planktonic alga Kirchneriella aperta was grown in batch cultures to stationary growth phase. Copper and lead complexation properties of the exudate from stationary and exponential growth phases were determined by titrations monitored by ion-selective electrodes. Molecular weight fractionation dialysis) and analysis of the titration data (Scatchard Plot) revealed that K. aperta releases metal-complexing ligands. Copper is associated with low and high molecular weight compounds, whereas lead forms complexes with only high molecular weight compounds. Gas-liquid chromatography showed that mannose and rhamnose make up 74% of the total high molecular weight organic material, with uronic acids present at 19%.
Keywords: alga; copper; gas chromatography; Kirchneriella aperta; lead; liquid chromatography; mannose; rhamnose; secondary metabolite